Estimating and Recapitalizing the Clients Reviews Efficiently on Snare - Kavyashree, BL; Nandhish, AC (International Journal of Computer Sciences and Engineering, 2025)
In this paper, the utilization of some of the large amount of data are inculcated to the users by some of the recommended products that are readily available. According to this the performance reliability of the particular product depends on the customers reviews so as to implement the relatively accessible cases in order to get the relevant manufactured articles that are attempting to get purchased from the customers who are ready to buy those products. The problem here is that the recommended system is being used only by the Amazon users. Therefore this paper is being presented for the utilization of other users also. Effectively the customer gets the reviews from the website in the same way in this paper the scanning of the barcode of the particular product is being introduced in order to inculcate the exact resources that are mandatorily introduced so as to perform the basic reviews of some of the similar products. Lastly the description of the product, name of the product, quality of the product needs as well as the summaries and reviews will be expected as the results.